Research on the Cultivation of College Students’ Innovation Ability and the Development of Self-Survival Innovation Team from the Perspective of Green Ecology - Yuwei Dong; Qingren Cao (Discrete Dynamics in Nature and Society)
Self-survival innovation teams composed of college students are considered incubators for future entrepreneurs. Stability is the prerequisite for team survival, while sustainable development is the necessary condition for their continuous progress. The development of members and the team are interrelated. In the continuous development of the team, the members, who contribute to the development of the team, change iteratively, while the team provides opportunities and platforms for the development of the members. However, at present, there are few researches on the sustainable development of the team and the data analysis on the correlation between the member development and the team construction. Therefore, in order to make a systematic analysis on the sustainable development ability of the team, this paper adopts questionnaires to obtain relevant information about college students and their innovation team. SPSS software (25.0) is used to make statistical analysis on the current development of college students’ individual ability and innovation team. Based on this, the paper puts forward analysis strategies for the personal development of college students and the construction of self-survival innovation team.